Drug resistance and plasma viral RNA level after ineffective use of oral pre-exposure prophylaxis in women. (28th January 2015) - Grant, Robert M.; Liegler, Teri; Defechereux, Patricia; Kashuba, Angela D.M.; Taylor, Douglas; Abdel-Mohsen, Mohamed; Deese, Jennifer; Fransen, Katrien; De Baetselier, Irith; Crucitti, Tania; Bentley, Gordon; Agingu, Walter; et al.
<x xml:space="preserve">Abstract</x> Background: Pre-exposure prophylaxis (PrEP) with daily oral emtricitabine (FTC)/tenofovir disoproxil fumarate may select for drug resistance if there is low adherence. Methods: Plasma viral HIV-1 RNA level, CD4+ T-cell counts, and drug resistance were evaluated among seroconverting women in the FEM-PrEP trial (clinicaltrials.gov NCT00625404) using standard clinical tests, allele-specific PCR (ASPCR), and by deep sequencing. Tenofovir, FTC, and their intracellular metabolites were measured in plasma and cells. Results: There was no difference in plasma HIV-1 RNA level or CD4+ cell count among seroconverters in the active arm versus those receiving placebo. Tenofovir resistance was not observed. FTC resistance was detected using clinical assays in five seroconverters (four in the active arm and one in the placebo arm); two in the active arm occurred among women having moderate concentrations of PrEP drugs in the blood. The first evidence of infection occurred at the first postenrollment visit in three of the four with FTC resistance, although none had detectable viral nucleic acids at enrollment. FTC-resistant minor variants were detected in an additional four seroconverters (one in the active arm and three in the placebo arm). Conclusions: Drug resistance detected during ineffective PrEP use had characteristics suggesting transmitted infection or incubating infection prior to starting PrEP.